morphological assessment of state myomatous tissue and different layers of myometrium at patients with uterus leiomyoma at preoperative correction of the hormonal status by means of Zoladex. - Medvedev, M. V. (Морфологія / Morphologia / Morfologìâ, 2011)
In research was spent mорmorphometric analysis of cellular, stromal and microvascular components of myomatous tissue and different layers of myometrium at 35 patients with uterus leiomyoma during long-term and short-term preoperative correction of the hormonal status by means of Zoladex®. Studying of specific volume of microvessels and stroma, quantitative density of myocyte nuclei and a mitotic index of myocytes was spent on sections in the thickness by 1 microns, made of epoxy blocks. Researches have shown, that in the conditions of 3-month’s medicamental menopause there is an authentic depression of specific volume of microvessels. In the conditions of the raised level of sexual steroids growth of contents of microvessels of myomatous nodes at the expense of dilating of arterioles and metarterioles lumen and thickening of their sides is observed. At simple myoma against a medicamental menopause the reduction of specific volume of stroma in myometriums submucous and vascular layers at that time in 1 week after introduction Zoladex the changes are not defined. In nodes of a cellular myoma in the conditions of long menopause it is observed more than double growth of relative contents of a stroma. In conditions hypohormonemia throughout 3 months there is depression of mitotic activity of nodal myocytes as a part of simple and cellular myoma. On the contrary, against hyperhormonemia in 1 week of Zoladex action essential is rising of a mitotic index of myocytes of cellular leiomyoma is observed.